1974
DOI: 10.1073/pnas.71.10.4173
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Involvement of Sulfhydryl Oxidation in the Regulation of Fat Cell Hexose Transport by Insulin

Abstract: Previous studies have shown that the oxidants Cu++, H202, and diamide mimic the stimulatory effect of insulin on 3-0-methylglucose transport in isolated fat cells. The present experiments were designed to determine whether sulfhydryl oxidation plays a key role in the activation of the glucose transport system. It was found that reductants such as dithiothreitol inhibited 3-0-methylglucose transport rates and that this effect was reversible when cells were washed free of reducing agent. Treatment of cells with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
88
1

Year Published

1976
1976
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(93 citation statements)
references
References 17 publications
4
88
1
Order By: Relevance
“…A role for ROS in insulin-mediated signaling has been suggested by the observation that insulin stimulation induces the rapid production of ROS and that H 2 O 2 can mimic some of the action of insulin (Czech et al, 1974;KriegerBrauer et al, 1997). Recent reports (Mahadev et al, 2001a;Mahadev et al, 2001b) have demonstrated that insulin-stimulated ROS generation modulated the steady-state tyrosine phosphorylation of the insulin receptor and its cellular substrates by reversible inhibition of PTPases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A role for ROS in insulin-mediated signaling has been suggested by the observation that insulin stimulation induces the rapid production of ROS and that H 2 O 2 can mimic some of the action of insulin (Czech et al, 1974;KriegerBrauer et al, 1997). Recent reports (Mahadev et al, 2001a;Mahadev et al, 2001b) have demonstrated that insulin-stimulated ROS generation modulated the steady-state tyrosine phosphorylation of the insulin receptor and its cellular substrates by reversible inhibition of PTPases.…”
Section: Discussionmentioning
confidence: 99%
“…Our data show that the insulin-mediated increase of PI-3 kinase activity is independent of ROS production and suggest that PI-3 kinase is not the major target of ROS. Moreover, these results suggest that the binding motifs of the p85 regulatory subunit of PI-3 kinase located in the insulin receptor or IRS are more resistant to the member of PTP family, the known target of the reversible inactivation by ROS, than other tyrosine phosphorylation sites.A role for ROS in insulin-mediated signaling has been suggested by the observation that insulin stimulation induces the rapid production of ROS and that H 2 O 2 can mimic some of the action of insulin (Czech et al, 1974; KriegerBrauer et al, 1997). Recent reports (Mahadev et al, 2001a;Mahadev et al, 2001b) have demonstrated that insulin-stimulated ROS generation modulated the steady-state tyrosine phosphorylation of the insulin receptor and its cellular substrates by reversible inhibition of PTPases.…”
mentioning
confidence: 99%
“…This can be oxidized readily by cellular activities associated with redox cycling (Nakamura et al, 1997;Denu and Dixon, 1998). More than 30 years ago, Czech et al (1974), documented the involvement of sulfhydryl oxidation in insulin signaling, which more recent studies have shown to be mediated through one of the cysteine residues of PTP1B. It is interesting to note that insulin positively regulates Srx transcription and protein expression (Figure 4), which in turn can promote a negative regulatory activity on insulin signaling.…”
Section: Discussionmentioning
confidence: 99%
“…These include anti-(insulin receptor) antibodies (Kahn et spermine (Lockwood & East, 1974), vitamin K5 (Livingston et al, 1977, and H202 (Czech et al, 1974;May & de Haen, 1979). Among these, only orthovanadate has been reported to increase the tyrosine phosphorylation of the fJ subunit of insulin receptors in an intact cell system (Tamura et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…One example of these agents is H202. Although this is a simple molecule it is able to stimulate 3-O-methylglucose uptake (Czech et al, 1974), lipogenesis (May & de Haen, 1979), and to activate pyruvate dehydrogenase (May & de Haen, 1979). Using the rat hepatoma cell line H-35, in this study we have examined the possibility that H202 elicitates its insulin-like effects by stimulating tyrosine phosphorylation of the insulin receptor and activating its receptor kinase.…”
Section: Introductionmentioning
confidence: 99%